Characteristics of Kawasaki Disease Before and After the COVID-19 Pandemic in a Large Pediatric Heart Disease Center - Yu, Huan; Ni, Chao; Xia, Yuhan; Li, Jie; Hang, Biyao; Han, Cheng; Xu, Zhipeng; Luo, Ming; Rong, Xing; Zhu, Jinshun; Chu, Maoping (Frontiers in Pediatrics, 2022)
Abstract Background: Kawasaki disease (KD) is an acute febrile systemic vasculitis of unknown etiology. After the pandemic of coronavirus disease 2019 (COVID-19), some children infected by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) showed clinical symptoms similar to KD, indicating a close relationship between KD and SARS-CoV-2. Therefore, we designed this retrospective study to analyze the characteristics of KD patients before and after the COVID-19 pandemic. Methods: We retrospectively collected demographic and laboratory data of KD patients in Yuying Children's Hospital of Wenzhou Medical University from 1 January 2015 to 31 December 2020. Yuying Children's Hospital of Wenzhou Medical University is located in eastern China and is the largest pediatric heart disease center in the region, which includes a population of nearly 10 million. We studied the characteristics of KD patients and analyzed the changes in these characteristics before and after the emergence of SARS-CoV-2 in this area. Results: The analysis revealed the following novel features: (1) Under the influence of the COVID-19 pandemic, the onset age of Kawasaki disease became younger. (2) After the occurrence of COVID-19, the hospitalization days of KD patients were shorter than before the pandemic. (3) After the occurrence of COVID-19, the albumin of KD patients was higher than before the pandemic. (4) The COVID-19 pandemic did not have a significant effect on the incidence of coronary artery lesions (CALs) in Kawasaki disease. Conclusion: After the COVID-19 outbreak, the characteristics of KD patients showed a younger trend of age, shorter hospitalization days and higher levels of albumin, but the incidence of CALs did not change significantly.